Implementasi Moderasi Beragama dalam Pembentukan Akhlak Mulia sebagai Inovasi Pendidikan Humanis Ramah dan Damai - Zumrud, Azzah (MJI Publisher by PT Mitra Jurnal Indonesia, 2024)
Abstract This article explores the implementation of religious moderation in education as an innovation to shape noble character, tolerance, and harmony within society. This approach integrates religious and humanitarian values, focusing not only on cognitive aspects but also on the development of students' character and social attitudes. Based on studies in Islamic and general schools, the implementation of religious moderation has proven effective in instilling values of tolerance and noble character, despite challenges such as cultural resistance and limited resources. By integrating the thoughts of Imam Al Ghazali and Syed Muhammad Naquib Al Attas, this article emphasizes the importance of balancing spiritual and humanitarian development in education. Innovations such as learning modules, teacher training, student exchanges, and the utilization of technology and community are key steps to enhance the positive impact of this approach. Abstrak Artikel ini mengeksplorasi implementasi moderasi beragama dalam pendidikan sebagai inovasi untuk membentuk akhlak mulia, toleransi, dan harmoni di masyarakat. Pendekatan ini memadukan nilai-nilai agama dan kemanusiaan, tidak hanya fokus pada aspek kognitif tetapi juga pada pengembangan karakter dan sikap sosial siswa. Berdasarkan studi di madrasah dan sekolah umum, implementasi moderasi beragama terbukti efektif dalam menanamkan nilai-nilai toleransi dan akhlak mulia, meskipun menghadapi tantangan seperti resistensi budaya dan keterbatasan sumber daya. Dengan mengintegrasikan pemikiran Imam Al Ghazali dan Syed Muhammad Naquib Al Attas, artikel ini menekankan pentingnya keseimbangan antara pengembangan spiritual dan kemanusiaan dalam pendidikan. Inovasi berupa modul pembelajaran, pelatihan guru, pertukaran siswa, serta pemanfaatan teknologi dan komunitas menjadi langkah penting untuk memperkuat dampak positif dari pendekatan ini.